Kinetics of serum antibody response to Newcastle disease vaccine in Aseel, Kadaknath and White Leghorn chicken using ELISA - KOKATE, LAXMIKANT SAMBHAJI; KUMAR, SANJEEV; RAHIM, ABDUL; DAS, ANANTA KUMAR (The Indian Journal of Animal Sciences, 2017)
The study aimed to evaluate kinetics of serum antibody response to Newcastle disease (ND) vaccine investigating 120 chicks from Aseel, Kadaknath and White Leghorn (WLH) maintained at this institute. The day-old chicks were vaccinated with a dose of 106.5 EID50 of live attenuated ND vaccine F1 strain through occulo-nasal route followed by a booster dose on 28th day. The antibody titre means were estimated and varied significantly among different dpi in Aseel, Kadaknath and WLH. The immune sera in Aseel and Kadaknath had gradual inclining antibody titre levels for longer dpi with the highest titre means at 42 dpi, whereas the sera in WLH had an irregular trend in antibody levels with the highest titre mean at 7 dpi. Aseel, Kadaknath and WLH also varied in mean antibody titres at 7, 14 and 42 dpi. The highest titre means at each 7 and 14 dpi were in WLH followed by Aseel and Kadaknath, respectively, whereas at 42 dpi was in Aseel followed by WLH and Kadaknath. The results indicated importance of the vaccination of day-old chicks against ND to enhance maternal derived antibody response and also speak about much better antibody response to NDV in Aseel and Kadaknath native fowl.